A Buddhist Response to the Quality-Combination Problem for Panpsychism. (18th January 2022) - Chadha, Monima
Abstract: Abhidharma Buddhist philosophy presents a version of what is now often called "panprotopsychism." The most pressing group of problems for the Abhidharma panprotopsychism, like all other panpsychist views, is what Seager calls "the combination problem." There are at least three versions of the problem: the subject-combination problem; the quality-combination problem; and the structure-combination problem. I begin with the Abhidharma Buddhist version of panprotopsychism and its account of conscious experience. The main focus of this paper is to show that Abhidharma panprotopsychist account of conscious experience solves the quality-combination problem. In the last and closing Section, I look at other versions of the combination problem, primarily the subject-combination problem and the structural problem and provide a sketch of the Abhidharma Buddhist response to these.